EVALUATING HUMAN DIMENSION VARIABLES AND THEIR CONTRIBUTION TOWARDS OPERATIONAL READINESS IN THE ROYAL MALAYSIAN POLICE FORCE - Inderjit , S; Kwong , Fook Wen; Al Banna, Hasan; Wong, Wai Loong; Ong , Jessica Hai Liaw (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The operational readiness of law enforcement agencies, such as the Royal Malaysian Police (RMP), is critically influenced by various human dimension factors, including quality of life, morale, and psychological well-being. Research indicates that intangible human factors are critical for operational success and include aspects such as leadership, teamwork, quality of life, morale, psychological factors, resilience, trust, and organizational culture. Operational readiness encompasses the preparedness of the police force to respond efficiently to various incidents, ensuring public safety and effective crime prevention. Mental health issues, which are prevalent in high-stress environments like policing, can severely affect officers’ performance and overall operational readiness. Police officers often operate in high-stress environments, which can lead to decreased morale and compromised psychological well-being. There is a lack of comprehensive studies specifically examining how these human dimension factors interact and influence the operational readiness of the RMP. This gap in research presents a significant challenge, as it hampers the development of targeted interventions that could enhance the effectiveness of the police force. This research aims to analyse these factors, providing insights that can enhance operational effectiveness among the RMP personnels. By identifying and measuring these human intangible factors, RMP can develop preventive measures that enhance overall operational effectiveness. This research is pivotal for ensuring that the Royal Malaysian Police and other security agencies are not only equipped with the necessary tools and technology but also possess the human capabilities required to face modern security challenges. By focusing on the human dimension, the research contributes to a more holistic and sustainable approach to national and global security.